Rethinking "State Shinto" in the Past and the Present - Okuyama, Michiaki (Numen, 2019)
This article reflects on the meaning of recent arguments concerning "State Shinto" in the contemporary Japanese right-wing and conservative social context. Shimazono Susumu's recent analyses of State Shinto in postwar Japan have stimulated discussion of the subject. His understanding that State Shinto has survived from the prewar years is based on his analysis of both Imperial House Shinto, which was not affected by the Shinto Directive issued in 1945, and the postwar political activism of the Association of Shinto Shrines and its political arm, the Shinto Association for Spiritual Leadership. The political campaigns of these Shinto groups can be situated in a larger context of the rise of neonationalism in contemporary Japanese society. Given the relationship of Japanese politicians to the Yasukuni Shrine and Ise Jingū (Ise Shrine), and the current interest among the public in the rituals of the emperor and the imperial family, a reconsideration of the concept of State Shinto seems warranted. A critical rethinking of State Shinto may be regarded as a warning against attempts by conservative religio-political movements to revive prewar State Shinto.